Swyer’s syndrome: a rare cause of primary amenorrhoea - Naik M.V., Kusuma; A.H., Nusrat; L, Krishna; Patil, Avinash; ., Pallavi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
This is a rare case of pure gonadal dysgenesis, the exact incidence of the condition is unknown but can be estimated at 1:80 000 births. The patient presented with primary amenorrhoea , after complete evaluation it was diagnosed as Swyer’s syndrome, which is 46,XY complete gonadal dysgenesis (46,XY CGD) characterized by a 46,XY karyotype, normal female external genitalia, completely undeveloped (”streak”) gonads, no sperm production, and presence of normal müllerian structures.